(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article is written on the topic "Using Active Games to Improve Physical Training in Young Athletes" and explores the importance of active games in the physical training process of young athletes. The article analyzes the role of active games in physical development, skill formation, and increasing athletes’ motivation. The results of research conducted based on a questionnaire are presented, demonstrating the benefits of these games for young athletes. Additionally, the article provides recommendations on how to effectively incorporate active games into physical training programs. The findings of this research are of significant importance in the field of sports education and physical training, helping to further improve the training process for young athletes.